A new concept of wood bonding design for strength enhanced southern yellow pine wood products. (30th December 2017) - Liu, Ming; Wu, Yiqiang; Wan, Hui
Graphical abstract: Highlights: The compression features of early/late wood of southern yellow pine were studied. The radial section wood samples were used to develop a better bonding design. The new conceptual design has fully utilized the southern yellow pine features. Compared to conventional way, the new design has improved dry bonding strength. Wood density might be the main factor for fully exploiting the design. Abstract: Bonding strength in the structure of engineered wood products and composites is one of the vital properties for their application. Up to now, numerous research efforts have been made on improving durability, wettability, and strength of resins or adhesives. However, there are only a few reports on how to improve bond line strength according to wood feature itself. In this study, a new conceptual bonding design based on wood radial section feature was reported. In this design, finger-joint like bonding interfaces were generated by hot pressing two resin coated wood radial sections together at optimized pressure of 300 lb per square inch (psi). By this design, the wet bonding strength of the bond line has potential to be higher than dry bonding strength. Meanwhile, with a compression ratio of 7.3% of wood strips, the obtained dry bonding or shear strength has been significantly increased up to 33.9%, as compared to end matched tangential controls. Wood specific gravity played an important role in this design. A proper compression ratio explored here in the radial section was about 17%. This work has provided a new route to improve wood bonding strength in an environmentally friendly way. Its impact on bending strength and dimensional stability of bonded wood structures needs to be further investigated.